P141 Unwarranted variation in chronic obstructive pulmonary disease care: provision of pulmonary rehabilitation for Londoners. (2nd December 2011) - Buxton, M; Prigmore, S; Barnes, K; Coombes, A; Williams, S; Restrick, L
Abstract : Introduction and Objectives: Pulmonary Rehabilitation (PR) is recognised as an essential component of care for patients with chronic obstructive pulmonary disease (COPD). However there is no national database of available or delivered PR services. The aim of this study was to identify and characterise PR services and service variation for a 7.75 million population in one Health Authority with 31 Primary Care Trusts (PCTs). Methods: PR leads in each PCT were identified and a telephone interview conducted using 52 clinical and service related questions including estimated annual referrals, rolling/cohort model, sessions/week, PR duration, assessment (duration, exercise capacity (Incremental Shuttle Walk (ISW), 6 min Walk Test (6MWT)) and quality of life (QOL) measures), psychologist involvement, completion measures and availability of post PR-maintenance programmes. Provision of PR was compared to quality outcomes framework (QOF) prevalence of diagnosed COPD. Results: 26/31 (84%) PCTs provide PR (74 programmes) from 32 service providers; 5 PCTs provide no PR. Provision was not related to COPD prevalence; the range of service referrals received was <50 to >700/year. 15/26 (58%) PCTS offered maintenance programmes. 52 programmes were rolling, 22 cohort, programme duration 6–8 weeks. 31/32 services provide 2 sessions/week (1 service 1 session/week); 15/32 (47%) services had psychology input. Assessments took 0.5–2 h/patient. 32/32 (100%) services used walking tests and 11/32 (34%) followed repeat walk guidance; 11/23 ISWT, 0/9 6MWT. Questionnaires used ranged between 1 and 5, 13/32 (41%) services used more than two questionnaires (See Abstract P141 table 1 below). (insert table as separate attachment) There was no standard definition of completion; range 50%–100% sessions attended. The range of estimates of completion rates (using own definitions) was <30% to >80%. Conclusions: PR is not available in five PCTs, despite evidence for its value, and capacity does not match need. Half of PCTs offer post-PR programmes reflecting demand from patients who complete PR. Studies of the value of maintenance PR are now needed. Reducing unwarranted variation in assessment process (questionnaires and walking tests), and completion (definition and rates) using standardised approaches to delivery and measurement would potentially release capacity for unmet need.